Stabilization of beam instability as a result of development of local instability in wave-wave interaction - Buts, V.А.; Kovalchuk, I.K.; Kornilov, E.A.; Tarasov, D.V. (Вопросы атомной науки и техники, 2003)
The new mechanism of stabilization of beam instability is proposed. The considered mechanism plays a special role at stabilization of beam instability in plasma systems with small size of interaction area of a beam of particles with field of exited waves. The basis of this mechanism is the process of three-wave decay with participation of a wave which easily abandons the field of interaction and also the process of chaotization of the fields at nonlinear interaction of waves.